Student satisfaction with the quality of educational performance during the COVID-19 pandemic From the perspective of a sample of students from the " Faculty of Medicine at the University of Tripoli " (Journal of human and social sciences, 2026)
This study aimed to recognize the impact of student satisfaction in Libyan universities during the Corona pandemic duration (COVID-19) on the quality of the performance of the educational process. The study relied on the descriptive approach in describing and analyzing the problem. Given that the study population is considered symmetrical and equal, it goes through the same academic conditions and is subject to one laws and regulations in all Libyan universities, except for some organizational points related to private higher education. The third semester students for the academic year 2021/2022 at the Faculty of Medicine, University of Tripoli, those affiliated with the group (AN132). They were 450 students, (151) students from the research group were questioned and fully respond to an electronic questionnaire that was prepared for the purpose of collecting data and information. The study reporting the impact of students satisfaction as statistically affecting the quality of the educational process during the pandemic (COVID-19).The results of the study also showed, according to the opinions of the study sample, that changes in the quality of the educational process were caused by students' satisfaction in its various dimensions and in a successive manner (university infrastructure, electronic interaction, evaluation methods, evaluation procedures, precautionary measures). Likewise, in terms of those who had contracted coronavirus disease (covid-19), the proportion of (55.6%) of the total study sample, while the number of those who received at least one vaccination dose reached a rate of 90.7%.The study recommended reconsidering and developing the dilapidated infrastructure, creating educational service facilities at the university, providing appropriate means of explanation for students, raising the level of education and health awareness among university pioneers, especially the students’ category, through awareness lectures, scientific conferences and seminars, in order to consolidate the culture of dealing with crises, and the development of new assessment methods for levels of education. Students, especially in the case of Online study and during periods of crisis.